Pengaruh Variasi Evaporator Terhadap Unjuk Kerja Mesin Pendingin Menggunakan Refrigerant R134a - Suyanto Suyanto; Ari Setiawan (Marine Science and Technology Journal, 2022)
Cooling machines are currently equipment that cannot be separated from human life. For this reason, a lot of research on cooling machines has been carried out to further optimize the work of the machine. This research was conducted to determine the effect of variations in the length of the evaporator pipe on the performance of the cooling machine. Evaporator pipes are varied with a length of 1 meter, 2 meters, and 3 meters. Other parameters are the length of the condenser pipe of 10 meters, the length of the capillary tube of 1.6 meters, and the freon pressure of 10Psi. Based on the results of measurements and calculations of 3 types of evaporator pipe variations, it can be concluded that variations with 1 meter long evaporator pipe get the best results, namely with an average low temperature of 0,920C, a refrigeration effect of 113.53 kJ/kg, and a COP of 2.62.